AN ANALYSIS OF THE COMPLEX SENTENCES USED IN THE THESES WRITTEN BY ENGLISH DEPARTMENT GRADUATES OF MARCH 2017 PERIOD IN UNIVERSITAS NEGERI PADANG - Danisa Warni; Yenni Rozimela; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
Abstract This research is a descriptive research which aims to observe the types of complex sentences in the theses written by graduates of English department graduates of March 2017 periode in Universitas Negeri Padang. The source of the data for this research are the theses written by English department graduates of March 2017 periode in Universitas Negeri Padang. There are 20 of 73 theses chosen as sample for this research by using purposive random sampling. Based on the research, there are three types of complex sentences within the theses namely noun clause, adverbial clause and adjective clause. The result of the analysis shows that there are 210 complex sentences from 20 theses. There are 23 sentences are categorized as noun clause, 126 as adverbial clauses and 61 adjective clauses. The most type used is the adverbial clause. It is found that 92 of 210 sentences are categorized very good, 110 are good, 8 are sufficient and 0 are poor. The adverbial clauses are the most used type of the sentences and followed adjective clause.Key words: Complex Sentence Types, Theses